Central American Tax Reform : Trends and Possibilities - Stotsky, Janet; WoldeMariam, Asegedech (Washington, D.C. : International Monetary Fund, 2002)
Central American tax systems are modern in their orientation, though there remains scope for beneficial reform. Value-added taxes are the mainstay of collections, but their performance varies. Income and property taxes remain relatively underused and should apply to higher income taxpayers more comprehensively. Tax reform needs to be mindful of global competition. Continuing improvement in administrative performance is also essential.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet